Educação Física Escolar e a prova do ENEM: convergências e divergências - ZAGHI, Flávio Henrique Lara da Silveira (2014)
Since 1996 Physical Education is ensured by law curriculum as a mandatory component of basic education, but much has been discussed about the legitimacy of this discipline in the school context. In 2009 there was an event that can be considered a watershed for this area of knowledge that is the entrance of Physical Education in the National Secondary Education Examination (ENEM). - Investigate whether the contents of the Physical Education area presented at the National High School Exam (ESMS), are present in the physical education classes of secondary education schools Passos - MG. In seeking to achieve success, the literature review encompassed topics such as the discussion about the legality x legitimacy, participation, student motivation towards physical education classes in school as well as the contents of this curriculum component. In a second step, we bring as a matter of high school reform and its new propositions, based on official documents, and finally, the relationship between school physical education and Enem. The field research, a qualitative approach was used recorded interviews with structured questions related to the proposed 22 physical education teachers who teach in high school in a city in the state of Minas Gerais theme. For data analysis proposed by Moreira, Oporto and Simões (2005) technique was used. The results showed that teachers find it difficult to define the objectives, content and methodology of teaching Physical Education in High School. Predominance for sports and teaching methodology is guided movements that meet the given sports. Include, in general, teachers have clarity about the social-political Enem function, and few bother to teach in their classes, the contents of the Physical Education who are present at the examination. Thus we can see that there is a mismatch between school physical education and Enem that most teachers are unaware of what is being charged and not even bother to teach the contents contained on the exam. Thus, the impact of the entry of Physical Education in Enem, was minimal, but important to the area, to leave the stage we are in, between "no more and no further".